(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
The article establishes that if the condition is met that the short fibers scraped off in the upper chamber of the delinter move along the surface of the combined saw-metal brush cylinder, then fibers of such mass will remain on the surface of the combined saw-metal brush cylinder, and if, then such a short fiber will separate from the surface of the combined saw-metal brush cylinder and turn into free fibers. Data on the optimal parameters of the delinter in the conducted multifactorial experiments are presented.